'A woman's place…': community-based approaches to gender-based violence in Malawi. (30th August 2017) - Gaynor, Niamh; Cronin, Máirtín
Abstract: One in five women has experienced gender-based violence (GBV) in Malawi and its incidence is reported to be increasing. The importance of cultural norms, practices, discourses and behaviours in both driving and addressing such violence is now well recognized. So too is the attendant need to involve men as well as women in community interventions to address this. In this context, this article draws on field research conducted in 2016 in two districts in Northern and Southern Malawi exploring the successes and challenges posed by community-based approaches (CBAs) to tackling GBV. We find that CBAs have yielded a number of successes – notably a reported reduction in GBV as communications between couples have improved and economic stresses within households reduced. However, we also find that these same CBAs have raised a number of challenges. These centre around resource distribution; the impact on local power dynamics; and CBA's ability to challenge and interrogate dominant norms, ideologies, identities and practices. Overall, we argue that, while CBAs appear successful in transmitting the message to both women and men that GBV is unlawful and wrong, their impacts on the principal underlying causal factors remain weak.